Proteome Analysis of Date Palm (Phoenix dactylifera L.) under Severe Drought and Salt Stress. (20th October 2016) - El Rabey, Haddad A.; Al-Malki, Abdulrahman L.; Abulnaja, Khalid O.
Abstract : Date palm cultivars differently tolerate salinity and drought stress. This study was carried out to study the response of date palm to severe salinity and drought based on leaf proteome analysis. Eighteen-month-old date palm plants were subjected to severe salt (48 g/L NaCl) and drought (82.5 g/L PEG or no irrigation) conditions for one month. Using a protein 2D electrophoresis method, 55 protein spots were analyzed using mass spectrometry. ATP synthase CF1 alpha chains were significantly upregulated under all three stress conditions. Changes in the abundance of RubisCO activase and one of the RubisCO fragments were significant in the same spots only for salt stress and drought stress with no irrigation, and oxygen-evolving enhancer protein 2 was changed in different spots. Transketolase was significantly changed only in drought stress with PEG. The expression of salt and drought stress genes of the chosen protein spots was either overexpressed or downexpressed as revealed by the high or low protein abundance, respectively. In addition, all drought tolerance genes due to no irrigation were downregulated. In conclusion, the proteome analysis of date palm under salinity and drought conditions indicated that both salinity and drought tolerance genes were differentially expressed resulting in high or low protein abundance of the chosen protein spots as a result of exposure to drought and salinity stress condition.